Customized design and additive manufacturing of kids’ ankle foot orthosis - Banga, Harish Kumar; Kalra, Parveen; Belokar, Rajendra M; Kumar, Rajesh (Rapid prototyping journal, 2020)
Purpose The purpose of this study is improvement of human gait by customized design of ankle foot orthosis (AFO). An has been the most frequently used orthosis in children with cerebral palsy. AFOs are designed to boost existing features or to avoid depression or traumatize muscle contractures. The advantages of AFO’s utilized for advancement in human walk attributes for the improvement in foot deformities patients or youngsters with spastic loss of motion. In this research on the customized design of AFO's to improve gait, there are limitations during walking of foot drop patients. In children with foot drops, specific AFOs were explicitly altered to improve parity and strength which are beneficial to walking positions. Design/methodology/approach This study proposes the customized design of AFOs using computerized and additive manufacturing for producing advances to alter the design and increase comfort for foot drop patients. Structuring the proposed design fabricated by using additive manufacturing and restricted material, the investigation was finalized at the Design Analysis Software (ANSYS). The system that performs best under investigation can additionally be printed using additive manufacturing. Findings The results show that the customized design of AFOs meets the patient’s requirements and could also be an alternative solution to the existing AFO design. The biomechanical consequences and mechanical properties of additive manufactured AFOs have been comparable to historically synthetic AFOs. While developing the novel AFO designs, the use of 3D printing has many benefits, including stiffness and weight optimization, to improve biomechanical function and comfort. To defeat the issues of foot drop patients, a customized AFO is used to improve the human gait cycle with new material and having better mechanical properties. Originality/value This research work focuses on the biomechanical impacts and mechanical properties of customized 3D-printed AFOs and compares them to traditionally made AFOs. Customized AFO design using 3D printing has numerous potential advantages, including new material with lightweight advancement, to improve biomechanical function and comfort. Normally, new applications mean an incremental collection of learning approximately the behavior of such gadgets and blending the new design, composite speculation and delivered substance production. The test results aim to overcome the new AFO structure issues and display the limited components and stress examination. The outcome of the research is the improved gait cycle of foot drop patients.